Collaborative, Problem-based Learning On-line: Developing a Multimedia Case Study Approach - Levy, Philippa; Bacigalupo, Ruth; Bath, Peter; Eaglestone, Barry; Booth, Andrew; Diercks-O’Brien, Gabi; Procter, Paula; Sanderson, Mark (Proceedings of the International Conference on Networked Learning, 2002)
This learning and teaching development project, funded by the University of Sheffield, is being carried out to enhance the learning experience of participants on a professional development Masters programme in Health Informatics. The project involves the introduction of problem-based, collaborative learning to the programme, through the vehicle of an extended, multimedia case study. The paper discusses the pedagogic rationale for this initiative, describes its main features and offers a reflection on a number of educational and project management issues that have arisen from the first phase of development, piloting and evaluation. The authors conclude by noting that although the project has entailed significant development investment, its impact already appears far-reaching in terms of both educational and staff development benefits.